NEW TENDENCIES IN TEACHING FOREIGN LANGUAGES AT TERTIARY LEVEL - E. N. Solovova (Vestnik MGIMO-Universiteta)
The article focuses on the perspectives of FL methodology at tertiary level and the nearest objectives for the system of upgrading professional qualification for the staff members of language chairs. There are some objective problems that universities face in respect to FL teaching that secondary schools don’t. The main problem lies in the lack of transparent and clear-cut system of expectations for the level of language proficiency for graduate students. The number of credits for the FL course at some universities is reducing, while the expectations are growing. It is crucial to develop national curriculum in FL teaching for different universities and departments majoring in Humanities, Arts, Science, Engineering, etc., otherwise it will be difficult to develop realistic syllabi and the system of FL assessment and evaluation In the process of curriculum and syllabus design it seems important to rethink the correlation between possible patterns of language use that are relevant for different target groups: EGP, EAP, ESP. In terms of achieving international academic mobility it is important to design new curriculum according to ECTS, to raise the degree of learners’ autonomy. It means new forms and formats of teacher- student and student-student interaction should be implied for contact hours and the system of independent work on the course. The role of IT and the transparent system of assessment in this respect needs to be predetermined. It is equally important to develop a feasible system of re-training staff members so that they could meet new challenges well equipped.